The role of IFN-γ/CXCL10 axis in Mycoplasma pneumonia infection - Yanxia Zou; Feng Huang; Jiying Sun; Yidan Zheng; Ge Dai; Ting Wang; Canhong Zhu; Yongdong Yan; Renzheng Wang; Zhengrong Chen (Scientific Reports)
Abstract Mycoplasma pneumoniae caused lower respiratory tract infection in children and can exacerbate these infections through the production of various inflammatory factors, with chemokines playing a key role. However, the pathogenesis of this infection is complicated and thus has not been thoroughly studied. We clarified that cytokine expression levels were analyzed in both peripheral blood and bronchoalveolar lavage fluid (BALF), and in vitro assays were conducted using THP-1 macrophages. We discovered that, compared to control children, M. pneumoniae pneumonia (MPP) patients expressed significantly higher levels of CXCL10 both in the peripheral blood and BALF. Moreover, numbers of macrophages, predominantly with a M1 phenotype, were significantly increased in BALFs of children of MPP. In vitro, coculture with IFN-γ or activated CD4+ Th1 cells significantly promoted CXCL10 expressions in THP-1 derived macrophages, which was largely reversed by siRNA-mediated down regulation of STAT1. In addition, IFN-γ-stimulated macrophages greatly promoted the trans-migration of Th1 cells. our data show that Th1 cells-derived IFN-γ augments CXCL10 production in macrophages via the JAK-STAT1 pathway, which subsequently recruits more immune cells like Th1 cells into the infection sites, thereby constituting a positive feedback loop and aggravating the type I inflammatory responses in MPP patients.